2011
DOI: 10.1186/bcr2901
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease competes with breast cancer as the leading cause of death for older females diagnosed with breast cancer: a retrospective cohort study

Abstract: IntroductionMany women who survive breast cancer die of causes unrelated to their cancer diagnosis. This study was undertaken to assess factors that are related to breast cancer mortality versus mortality from other causes and to describe the leading causes of death among older women diagnosed with breast cancer.MethodsWomen diagnosed with breast cancer at age 66 or older between 1992 and 2000 were identified in the Surveillance, Epidemiology and End Results-Medicare linked database and followed through the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
466
1
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 710 publications
(490 citation statements)
references
References 21 publications
12
466
1
11
Order By: Relevance
“…30 Therefore, modifiable risk factors and poor lifestyle choices can ultimately contribute to an increased cardiovascular disease risk among breast cancer survivors. 4,8,29,42 Additional studies indicated that African American breast cancer survivors were at an increased cardiovascular disease risk compared to other races. 23,31,36 Having a first-degree family history of heart disease also increased the cardiovascular disease risk.…”
Section: Modifiable Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…30 Therefore, modifiable risk factors and poor lifestyle choices can ultimately contribute to an increased cardiovascular disease risk among breast cancer survivors. 4,8,29,42 Additional studies indicated that African American breast cancer survivors were at an increased cardiovascular disease risk compared to other races. 23,31,36 Having a first-degree family history of heart disease also increased the cardiovascular disease risk.…”
Section: Modifiable Factorsmentioning
confidence: 99%
“…Cardiovascular disease risk was often conceptually defined as incidence of cardiovascular diseases including ischemic heart disease, congestive heart failure, myocardial infarction, coronary artery disease, stroke, angina, atrial fibrillation, paroxysmal tachycardia, nonrheumatic valve disease, cardiomyopathy, aortic aneurysm, and arteriosclerosis. [3][4]8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] While one study included angina as a cardiovascular disease risk factor, 15 Darby et al indicated that angina would not be included as a risk factor due to difficulty with clinical identification of angina. 19 Other investigators conceptually defined cardiovascular disease risk as the presence of cardiovascular disease risk factors including smoking and having an overweight or obese body mass index.…”
Section: Conceptual Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Patnaik and colleagues reviewed the Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database and found that breast cancer survivors were as likely to die from cardiovascular disease as from recurrent breast cancer. 3 Additionally, Mertens and colleagues found that cardiovascular events are the leading cause of nonmalignant deaths in survivors of childhood cancers. 4 Because of the ongoing need for recurrent cancer monitoring, the treating oncologist may be the de facto primary care physician for many oncologic patients.…”
Section: Cardio-oncology For the 21st Century: Introductionmentioning
confidence: 99%